Carbon and Oxide Nanostructures Synthesis, Characterisation and Applications - Yahya, Noorhana; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This volume covers all aspects of carbon and oxide based nanostructured materials. The topics include synthesis, characterization and application of carbon-based namely carbon nanotubes, carbon nanofibres, fullerenes, carbon filled composites etc. In addition, metal oxides namely, ZnO, TiO2, Fe2O3, ferrites, garnets etc., for various applications like sensors, solar cells, transformers, antennas, catalysts, batteries, lubricants, are presented. The book also includes the modeling of oxide and carbon based nanomaterials. The book covers the topics: -- Synthesis, characterization and application of carbon nanotubes, carbon nanofibres, fullerenes -- Synthesis, characterization and application of oxide based nanomaterials. -- Nanostructured magnetic and electric materials and their applications. -- Nanostructured materials for petro-chemical industry. -- Oxide and carbon based thin films for electronics and sustainable energy. -- Theory, calculations and modeling of nanostructured materials.
Synthesis of Carbon Nanostructures by CVD method -- Fullerenes (C60) and its Derivatives as Resist for Electron Beam Lithography -- Carbon Nanostructured Materials -- Hydrogenated Amorphous Carbon Films -- Carbon nanotubes Towards Organic Solar Cells.-Irregular Configurations of Carbon Nanofibers -- Molecular Simulation to Rationalize Structure-Property Correlation of Carbon Nanotube -- Carbon Nanotubes: The Minuscule Wizards- Diamond: Synthesis, Characterisation and Applications -- Versatility of ZnO Nanostructures -- Supported Nanoparticles for Fuel Synthesis.-Nanotechnology in Solar Hydrogen Production -- Fe-FeO nanocomposites: Preparation, Characterization and Magnetic Properties -- Nanostructured Materials Use in Sensors: Their Benefits and Drawbacks -- Zinc Oxide Nanostructured Thin Films: Preparation and Characterization -- Superparamagnetic Nanoparticles -- Ammonia Synthesis.
Electronic reproduction.
Keywords: Nanostructured materials; Nanostructured materials -- Design and construction; Nanotubes; Electronic books